Association between frailty and meaning in life of older adults in nursing home: the mediating effect of psychological resilience - Zhang, Jiquan; Xu, Fan; Zhou, Yang; Wu, Jijun; Li, Yuxin; Qing, Wei (Frontiers in Psychology, 2024)
Background Meaning in life is a crucial aspect of psychological well-being, often overlooked despite its clinical significance. This warrants further investigation, especially regarding its relationship with frailty and psychological resilience. Objective This study aims to assess the status and relevance of frailty, psychological resilience, and meaning in life among older adults in Chinese nursing homes. Additionally, it explores the mediating role of psychological resilience between frailty and meaning in life, providing insights to improve the meaning in life for older adults in nursing homes. Methods Between August 2022 and November 2022, 302 older adults in Chinese nursing homes were selected using convenience sampling. The study utilized the Socio-demographic Characteristics Questionnaire, Tilburg Frailty Indicator, Connor-Davidson Resilience Scale, and the Source of Meaning Scale for Older Adults. A face-to-face questionnaire survey was conducted, and SPSS 27.0 was employed for analyzing correlations between frailty, psychological resilience, and meaning in life. The mediating effect of psychological resilience was assessed using Model 4 in the Process plug-in. Results Older adults in nursing homes exhibited a frailty total score of 4.00 (2.00, 5.00), with a prevalence of 28.5%. Psychological resilience scored 66.00 (51.75, 76.00), and meaning in life scored 149.00 (132.00, 158.25). Frailty showed a negative correlation with both meaning in life and psychological resilience, while meaning in life demonstrated a positive correlation with psychological resilience. Psychological resilience exhibited a partial mediating effect, accounting for 51.04% of the total effect between frailty and meaning in life. Conclusion Frailty incidence is high among older adults in nursing homes, with psychological resilience at a general level and meaning in life in the upper middle level. Psychological resilience plays a crucial role as a partial mediator between frailty and meaning in life. Timely assessment of frailty, targeted interventions, and improvements in psychological resilience are essential for enhancing the meaning in life and promoting successful aging.